Carbon and Nitrogen Stocks in the Surface Mixed Layer of Seagrass Meadow Sediments across the Northern Gulf of Mexico - Kyle Capistrant-Fossa; Kelly Darnell; Kenneth Dunton (Estuaries and Coasts, 2026)
The Northern Gulf of Mexico (nGOM) is a hotspot for blue carbon biogeochemical cycles due to its ability to fix and sequester blue carbon and potential to mitigate rising atmospheric CO $$_2$$ concentrations. In this study, we employed a dataset containing >1100 sediment cores collected from seagrass beds paired with publicly available data to estimate C and N stocks within the surface mixed layer of seagrass meadows. Sediments directly beneath seagrasses were less dense (0.98 ± 0.23 g cm $$^{-3}$$ ) but contained more combustible matter (11.27 ± 6.99%) than surrounding bare patches, and the amount significant varied among seagrass species. We estimate that seagrasses contribute about half of sedimentary organic carbon across the region, but there is substantial variability in sources among bays. Sediments had more inorganic (6 ± 4.97%) matter than organic matter (4.38 ± 3.39%), and inorganic carbon stocks appear to be lower than those in other parts of the world. The upper 10 cm of sediment with seagrass beds across the nGOM are estimated to contain as much as 7.03 and 0.43 Tg of C and N, respectively, affirming their importance within global biogeochemical cycles.